1996
DOI: 10.1016/0014-5793(96)01121-0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ouabain‐sensitive 86Rb+ uptake and Na+,K+‐ATPase α‐subunit phosphorylation by a cAMP‐dependent signalling pathway in intact cells from rat kidney cortex

Abstract: We investigated in intact cortical kidney tubules the role of PKA-mediated phosphorylation in the short-term control of Na+,K+-ATPase activity. The phosphorylation level of Na+,K+-ATPase was evaluated after immunoprecipitation of the enzyme from 32p-labelled cortical tubules and the cation transport activity of Na+,K+-ATPase was measured by ouabainsensitive 86Rb + uptake. Incubation of cells with cAMP analogues (8-bromo-cAMP, dibutyryl-cAMP) or with forskolin plus 3-isobutyl-l-methylxanthine increased the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Recent studies in transfected cells indicate that serine-threonine phosphorylation of the catalytic ␣-subunit by PKA or PKC is a key event in the short-term regulation of Na ϩ ,K ϩ -ATPase activity (Fisone et al, 1994;Belusa et al, 1997;Pedemonte et al, 1997;Chibalin et al, 1998). The physiological relevance of this process is supported by the correlation between the phosphorylation level of the ␣-subunit and the activity of Na ϩ ,K ϩ -ATPase in response to PKA (Carranza et al, 1996b) or PKC activation (Carranza et al, 1996a) in isolated rat PCT. On the other hand, PKA and PKC phosphorylations do not fully account for the basal phosphorylation level of the ␣-subunit observed in various cells (Béguin et al, 1994;Carranza et al, 1996a,b), implying the likely presence of additional phosphorylation sites.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recent studies in transfected cells indicate that serine-threonine phosphorylation of the catalytic ␣-subunit by PKA or PKC is a key event in the short-term regulation of Na ϩ ,K ϩ -ATPase activity (Fisone et al, 1994;Belusa et al, 1997;Pedemonte et al, 1997;Chibalin et al, 1998). The physiological relevance of this process is supported by the correlation between the phosphorylation level of the ␣-subunit and the activity of Na ϩ ,K ϩ -ATPase in response to PKA (Carranza et al, 1996b) or PKC activation (Carranza et al, 1996a) in isolated rat PCT. On the other hand, PKA and PKC phosphorylations do not fully account for the basal phosphorylation level of the ␣-subunit observed in various cells (Béguin et al, 1994;Carranza et al, 1996a,b), implying the likely presence of additional phosphorylation sites.…”
Section: Introductionmentioning
confidence: 72%
“…Besides long-term regulation by steroid and thyroid hormones (Doucet et al, 1986;Barlet-Bas et al, 1987;Palmer et al, 1993), kidney tubule Na ϩ ,K ϩ -ATPase activity can be rapidly modulated through changes in cell surface expression (Beron et al, 1997;Carranza et al, 1998) and/or by modifications of the function of single-pump units (Féraille et al, 1994(Féraille et al, , 1995. In this regard, it has been demonstrated that the ␣-subunit of Na ϩ ,K ϩ -ATPase can be phosphorylated by PKA and PKC in vitro (Bertorello et al, 1991;Chibalin et al, 1992;Feschenko and Sweadner, 1995) and in intact cells (Middleton et al, 1993;Béguin et al, 1994;Féraille et al, 1995;Fisone et al, 1995;Carranza et al, 1996b). Recent studies in transfected cells indicate that serine-threonine phosphorylation of the catalytic ␣-subunit by PKA or PKC is a key event in the short-term regulation of Na ϩ ,K ϩ -ATPase activity (Fisone et al, 1994;Belusa et al, 1997;Pedemonte et al, 1997;Chibalin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of Na ϩ ,K ϩ -ATPase activity by DA in renal PCT involves the sequential activation of arachidonic acid, 20-HETE, and PKC (35). Although cAMP stimulation has been suggested to contribute to the action of DA (36,37), it is unlikely that it would be directly involved in Na ϩ ,K ϩ -ATPase regulation (phosphorylation of the ␣-subunit in renal PCT cells) because increased cAMP in this segment does not inhibit (7) but is rather associated with stimulation of Na ϩ ,K ϩ -ATPase activity (38). Accordingly, in this study phosphorylation of Na ϩ ,K ϩ -ATPase ␣-subunits was blocked by PKC-, but not cAMP-K, inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PLA 2 in endocytosis by activation PI 3-K activity is also supported by recent observations that endosomal fusion is blocked by inhibitors of PLA 2 and that this effect is prevented by arachidonic acid (Mayorga et al, 1993) Inhibition of Na ϩ ,K ϩ -ATPase by DA in renal PCT (Bertorello and Aperia, 1990;Takemoto et al, 1992) and in neostriatal neurons (Bertorello et al, 1990) requires the combined activation of both D 1 and D 2 receptors. Stimulation of cAMP production in renal PCT cells has been associated with phosphorylation of Na ϩ ,K ϩ -ATPase ␣ subunit and stimulation of its catalytic activity (Carranza et al, 1996b), whereas the inhibitory action of DA as well as endocytosis of the Na ϩ ,K ϩ -ATPase ␣ subunit is blocked by PKC inhibitors (Bertorello and Katz, 1993;Chibalin et al, 1997). Thus, it is likely that the inhibitory effect of DA on Na ϩ ,K ϩ -ATPase activity is mediated by PKC, and cAMP may be an important cofactor in this regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%